STRATEGI KOMUNIKASI PEMASARAN BISNIS KULINER DALAM PERENCANAAN PARIWISATA UNTUK IDE KREATIF YANG PERSUASIF - Masril, Febriani; Olivia, Adinda; Alvaro, Joshua Magnus; Syakilla, Bella; Maldin, Siska Amelia (JURNAL MATA PARIWISATA, 2025)
The culinary industry faces increasingly complex marketing communication challenges in the digital era, where business practitioners are required to develop creative and persuasive ideas to attract consumer attention amid intense competition. This research aims to analyse culinary business marketing communication strategies in creating persuasive, creative ideas to enhance attractiveness and communication effectiveness. The research method employs a literature study with a descriptive qualitative approach, analysing 15 previous studies within the last five years that discuss marketing communication strategies in the culinary business context. Research findings indicate that effective marketing communication strategies integrate digital approaches through social media, particularly Instagram, with the utilisation of persuasive elements such as influencers, social proof, and aesthetic visual content. Creative ideas prove to be primary differentiators in creating profound cognitive and affective experiences, while empowerment of local values and traditional identity becomes important competitive capital. Implementation of strategic planning models such as SOSTAC, SWOT, and IMC enables systematic and measurable communication. Post-COVID-19 digital transformation strengthens the importance of social media-based personal selling with responsive and empathetic approaches. Research conclusions demonstrate that the success of modern culinary marketing communication strategies lies in the ability to create authentic narratives, build emotional engagement with consumers, and adapt digital technology without losing brand identity. The combination of innovative creative ideas, strategic social media usage, and local value integration becomes an effective formula for building competitive advantage in the dynamic culinary industry.